The Importance of Assessing the Economic Indicators of Farms - Bahodirjon Nosirov; Dilobar Fakhriddinova (Genius Journals, 2023)
On the basis of the introduction of a platform based on digital technologies for the assessment of the economic efficiency of the agricultural enterprises in operation, opportunities for continuous assessment of their economic indicators will be created in each agricultural enterprise. As a result, the issues of ensuring the country's food security based on increasing the volume and quality of production at agricultural enterprises were highlighted.
Keywords: farms; economic indicators; Uzbekistan; economic efficiency